1992
DOI: 10.1007/978-94-011-2452-2
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Sea Food Chains and the Global Carbon Cycle

Abstract: A Series presenting the results of activities sponsored by the NA TO Science Committee, which aims at the dissemination of advanced scientific and technological knowledge, with a view to strengthening links between scientific communities.The electronic index to the NATO ASI Series provides full bibliographical references (with keywords and/or abstracts) to more than 30000 contributions from international scientists published in all sections of the NATO ASI Series. Access to the NATO-PCO-DATA BASE is possible i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(2 citation statements)
references
References 303 publications
(490 reference statements)
0
2
0
Order By: Relevance
“…The DFA's results of the Arctic HAUSGARTEN time-series (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) revealed strong relationships between the phytoplankton composition and concentrations of biogenic sediment compounds, indicating organic matter in surface sediments with the explanatory variables chosen for our analysis. Higher amounts of sedimentbound chloroplastic pigments seemed to provide additional food supply for meiofauna and megafauna, which resulted in increases in abundance with a time lag of 1-2 years in larger organism size classes, as also found in other deep-sea areas (Sibuet et al 1989;Rowe and Pariente 1992;Kröncke et al 2013b).…”
Section: Biological Responses To Crs and The Role Of Temperaturementioning
confidence: 67%
See 1 more Smart Citation
“…The DFA's results of the Arctic HAUSGARTEN time-series (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) revealed strong relationships between the phytoplankton composition and concentrations of biogenic sediment compounds, indicating organic matter in surface sediments with the explanatory variables chosen for our analysis. Higher amounts of sedimentbound chloroplastic pigments seemed to provide additional food supply for meiofauna and megafauna, which resulted in increases in abundance with a time lag of 1-2 years in larger organism size classes, as also found in other deep-sea areas (Sibuet et al 1989;Rowe and Pariente 1992;Kröncke et al 2013b).…”
Section: Biological Responses To Crs and The Role Of Temperaturementioning
confidence: 67%
“…Quantitative and qualitative changes in phytoplankton have unavoidable consequences at the other trophic levels. Several studies of benthic communities revealed that their diversity and function depended on the amount and quality of organic matter produced in the water column, even at extreme depths (Rowe and Pariente 1992;Clare et al 2017). The DFA's results of the Arctic HAUSGARTEN time-series (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) revealed strong relationships between the phytoplankton composition and concentrations of biogenic sediment compounds, indicating organic matter in surface sediments with the explanatory variables chosen for our analysis.…”
Section: Biological Responses To Crs and The Role Of Temperaturementioning
confidence: 99%